QUANTUM DOT-EMBEDDED POLYMER FILMS FOR FLEXIBLE PHOTONIC DEVICES: FABRICATION AND CHARACTERIZATION - Ardi Azhar Nampira; Roya Zahir; Omar Khan; Siti Shofiah (Research of Scientia Naturalis, 2025)
materials for photonic devices that can conform to non-planar surfaces. Quantum dots (QDs) are ideal candidates due to their size-tunable emission and high quantum yields, but their integration into durable, flexible platforms remains a key challenge. This study aimed to develop and characterize highly luminescent and mechanically flexible quantum dot-embedded polymer films as a robust platform for next-generation photonic applications. We fabricated composite films by embedding cadmium selenide/zinc sulfide (CdSe/ZnS) core-shell QDs into a polydimethylsiloxane (PDMS) polymer matrix via solution casting. The structural, optical, and mechanical properties were systematically investigated using transmission electron microscopy (TEM), UV-Vis absorption, photoluminescence (PL) spectroscopy, and cyclic bending tests. The results showed that TEM analysis confirmed a uniform dispersion of QDs within the PDMS matrix without aggregation. The composite films exhibited intense, stable photoluminescence, retaining the characteristic sharp emission of the colloidal QDs. Crucially, the films demonstrated exceptional mechanical flexibility, maintaining over 95% of their initial PL intensity after 1,000 bending cycles to a 5 mm radius. The optical properties remained stable under various strain conditions, proving the effective protection afforded by the polymer matrix. This work successfully demonstrates a scalable method for producing high-quality, flexible photonic materials.